2008
DOI: 10.1176/ps.2008.59.3.241
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Cognitive Remediation Among Inpatients With Persistent Mental Illness

Abstract: Cognitive remediation was a feasible treatment for this group of inpatients and more effective at improving cognitive functioning than a computer control intervention. Longer-term follow-up indicated that cognitive remediation was associated with better work outcomes, suggesting benefits in psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 26 publications
8
47
2
2
Order By: Relevance
“…COGPACK is a computerized, commercially available CR program developed for persons with severe mental illness, with demonstrated efficacy in schizophrenia. 26,28,29 The curriculum of COGPACK exercises used in the current study is similar to that used in past controlled trials. 22,26,30 The curriculum consists of a standardized set of computerized exercises that provides practice of the broad range of cognitive functions and overlaps with cognitive domains assessed by the MCCB-MATRICS.…”
Section: Neurocognitive Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…COGPACK is a computerized, commercially available CR program developed for persons with severe mental illness, with demonstrated efficacy in schizophrenia. 26,28,29 The curriculum of COGPACK exercises used in the current study is similar to that used in past controlled trials. 22,26,30 The curriculum consists of a standardized set of computerized exercises that provides practice of the broad range of cognitive functions and overlaps with cognitive domains assessed by the MCCB-MATRICS.…”
Section: Neurocognitive Interventionmentioning
confidence: 99%
“…Additional features of MRIGE that contribute to its feasibility for use in schizophrenia is that it provides individualized practice that is adjusted to patient performance levels and allows a high degree of control and autonomy to users, features that have contributed to the feasibility of computerized CR in schizophrenia. 26 The aim of the present study was to compare the effects of a 12-week CR program (CR alone), having demonstrated efficacy on neurocognition in the patient population included in the present study, with CR combined with MRIGE, a novel training program of emotion perception (CR + MRIGE), on measures of emotion perception, social functioning, and neurocogniton. Our hypothesis was that the combined CR + MRIGE intervention would result in greater improvements in social cognition and measures of social functioning compared with CR alone.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that patients in the CRT group demonstrated significantly greater improvements over 3 months than the control group in overall cognitive functioning, psychomotor speed, and verbal learning, and worked more weeks than the control group over the 12-month follow-up period. 59 These findings suggest that this program may be beneficial for patients with significant functional and symptomatic impairments.…”
Section: Monthsmentioning
confidence: 93%
“…For example, Lindenmayer et al evaluated the feasibility and efficacy of a CRT program for improving cognitive and work functioning for intermediate-to longstay psychiatric inpatients. 59 In this study, symptoms were assessed with the Positive and Negative Syndrome Scale at submit your manuscript | www.dovepress.com baseline, midtreatment, posttreatment, and at 6-month and 12-month follow-ups. Results indicated that patients in the CRT group demonstrated significantly greater improvements over 3 months than the control group in overall cognitive functioning, psychomotor speed, and verbal learning, and worked more weeks than the control group over the 12-month follow-up period.…”
Section: Monthsmentioning
confidence: 99%
“…A number of studies in the reviews we have summarized typically involved young-adult or middle-aged white males (27); however, skills training programs have been adapted successfully for Latino clients (36,48), including outpatient services for older people with psychotic disorders of long duration. Some studies have included substantial numbers of participants with different ethnic and racial backgrounds in their study samples (49), including a number of studies with participants who were predominantly African American (50,51). Examples of other cross-cultural studies include an RCT of illness self-management conducted with hospitalized individuals with schizophrenia in Japan (33) and an RCT of successful skill-building interventions conducted in a Chinese psychiatric hospital (52).…”
Section: Level Of Evidencementioning
confidence: 99%